1975
DOI: 10.1017/s0003356100041222
|View full text |Cite
|
Sign up to set email alerts
|

A note on the effect of twin births on production in the subsequent lactation

Abstract: SUMMARYA study of the British Friesian Cattle Society's herdbook for 1961 showed that twin births were registered from 323 cows which had borne single calves the year before, and which had 2009 contemporaries of the same age calving single births in the same two seasons and in the same herds.Least squares means of milk yield and fat percentage calculated from the truncated 305-day lactation showed that the twin mothers exceeded their contemporaries by 118±47 kg milk in lactations 2 days shorter. After correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The subsequent metabolism of the steroid oestradiol slows down the natural decline in follicle stimulating hormone, which means that follicles have more time to undergo physiological changes before they ovulate. (Bowman and Hendy, 1970;Hendy and Bowman, 1970;Bar-Sy rstad, 1977;Chapin and Van Vleck, 1980) bu t Anan and Bowman, 1974 ;Suchanek, 1977 ;Syrstad, 1977;Chapin and Van Vleck, 1980) but do not support results of (Auran, 1974;Syrstad , 1974;Wood, 1975;Kay, 1978;Wood, 1984;Eddy et al, 1991). In other studies reported by (Nielen et al, 1989;Bell and Roberts, 2007) there was no significant difference in 305-d milk yield between twin and single calvers.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The subsequent metabolism of the steroid oestradiol slows down the natural decline in follicle stimulating hormone, which means that follicles have more time to undergo physiological changes before they ovulate. (Bowman and Hendy, 1970;Hendy and Bowman, 1970;Bar-Sy rstad, 1977;Chapin and Van Vleck, 1980) bu t Anan and Bowman, 1974 ;Suchanek, 1977 ;Syrstad, 1977;Chapin and Van Vleck, 1980) but do not support results of (Auran, 1974;Syrstad , 1974;Wood, 1975;Kay, 1978;Wood, 1984;Eddy et al, 1991). In other studies reported by (Nielen et al, 1989;Bell and Roberts, 2007) there was no significant difference in 305-d milk yield between twin and single calvers.…”
Section: Resultsmentioning
confidence: 92%
“…Other factors have been found to be associated with twinning, including use of antibiotics or reproductive hormones, ovarian cysts, days open, and peak milk production (Pfau et al, 1948;Johansson et al, 1974;Nielen et al, 1989;Ryan and Boland, 1991;Lopez-Gatius et al, 1996;Kinsel et al, 1998;Wiltbank et al, 2000).Studies of the effects of twin births on milk production in the subsequent lactation are contradictory. Cows with twins had greater milk production than cows with singletons (Auran, 1974;Syrstad, 1974;Wood, 1975;Kay, 1978;Wood, 1984;Eddy et al, 1991) while in others lower milk yields were recorded (Bar-Anan and Bowman, 1974;Suchanek, 1977;Syrstad, 1977;Chapin and Van Vleck, 1980). Effect of twinning on birth weight, weaning weight and growth of calves has been investigated in several studies (Bellows et al, 1971;Turman et al, 1971;Bellows et al, 1974;Johansson et al, 1974;Davis et al, 1989;Gregory et al, 1990Gregory et al, , 1996Echternkamp and Gregory, 2002;Bell and Roberts, 2007).…”
mentioning
confidence: 99%
“…Twinning has decreased milk yield in some studies (2,11,14) but in others has increased yield (1,12,15). Effects of increased dystocia (5,9) or of prolonged calving interval following twinning (2,4,9,11) also are important considerations.…”
Section: Introductionmentioning
confidence: 99%
“…As milk yield cannot be measured directly in mice, any information on the exact relationship between litter size and milk yield will have to come from dairy records. Investigations of the relationship between twin birth and milk production in dairy cattle (SYRSTAD 1974;WOOD 1975) have shown an increased milk yield in lactations following twin births. Similar results were obtained by STEINE (1 975) analysing milk recording data from goats.…”
Section: Discussionmentioning
confidence: 99%